Military Service of Knights, Vogts and Village Mayors in the Kingdom of Poland under the Reign of Władysław II Jagiełło: Legal Regulations - Gryglewski, Krzysztof (Faces of War, 2024)
The reign of Władysław Jagiełło in Poland was highly significant. He not only established a new dynasty but also succeeded diplomatically and militarily in foreign policy. His forty-year reign was also a time of granting privileges, which was necessary to win the support of the nobility and to execute the king’s will. This led to changes in military obligations, allowing the nobility to gain prerogatives, including the right to war prisoners. The king also repeated and extended existing privileges, such as the right to be paid for military campaigns on foreign territory and the right to compensation for the losses of equipment and horses. These changes were significant both militarily and politically and reinforced the nobility’s power within the kingdom. Changes in military services of the feudal system in Poland, which occurred during the reign of Władysław II Jagiełło, were essential in understanding the future military evolution of the Polish army.